Lipoprotein(a) as predictor of coronary artery disease and myocardial infarction in a multi-ethnic Asian population. (May 2022) - Loh, Wann Jia; Chang, Xuling; Aw, Tar Choon; Phua, Soon Kieng; Low, Adrian F.; Chan, Mark Yan-Yee; Watts, Gerald F.; Heng, Chew-Kiat
Abstract: Background and aims: The role of Lp(a) in multi-ethnic Asian populations with coronary artery disease (CAD) has not been well established. The aims of this study were (i) to investigate whether Lp(a) is a predictor of CAD, and (ii) amongst patients with CAD, to ascertain whether Lp(a) is a predictor of acute myocardial infarction (AMI) and severity of CAD. Methods: We compared three cardiovascular phenotypes from patients recruited at coronary angiography. CAD was defined as ≥50% coronary artery stenosis and subdivided into a group with AMI history (CAD+AMI+) and a group without (CAD+AMI-). Minimal CAD group (CAD-) was defined as normal or <30% coronary artery stenosis and no AMI. The severity of CAD was defined using the modified Gensini score. Results: We studied 2025 patients comprising 94.5% men and 61.4% of Chinese ethnicity. The median Lp(a) level was highest in CAD+AMI+, followed by CAD+AMI- and CAD- (26.2, 20.1, and 15.8 nmol/L respectively). Similarly, the frequency of patients with Lp(a) ≥120 nmol/L were in the same order (11.8%, 9.1% and 2.4%). Lp(a) levels were highest among Asian Indians, followed by Malays and Chinese patients ( p  < 0.001). Lp(a) levels and Lp(a) ≥120 nmol/L were significant predictors of CAD (Odds ratio (OR) = 1.12 per 10 nmol/L increment, p  < 0.001, and OR = 5.41 p  = 0.004 respectively). Among patients with CAD, higher Lp(a) levels were associated with increased AMI risk (OR = 1.02 per 10 nmol/L increment, p  = 0.024). Lp(a) ≥120 nmol/L was positively associated with CAD severity ( p  = 0.020). Conclusions: Plasma Lp(a) concentration is a positive predictor of CAD and AMI in a mostly male South East Asian population. Graphical abstract: Image 1 Highlights: Higher Lp(a) levels were associated with increased coronary artery disease (CAD) risk in multi-ethnic Asians. Lp(a) was associated with increased acute myocardial infarction (AMI) risk and severity of CAD. Distribution of Lp(a) is a right skew pattern in Chinese, Malays and Asians Indians.